Welfare reform and repression in an autocracy: Bismarck and the socialists - Felix Kersting (European Historical Economics Society (EHES), 2022)
Can autocratic governments gain support by implementing a welfare reform and a repressive law? This paper studies a famous case - Bismarck's policies of social insurance and the antisocialist law in late 19th century Germany. The socialist party, I find, increases its vote share in constituencies more affected by Bismarck's policies. For identification, I exploit local and industry-specific variation in treatment intensity due to ex-ante existing local healthcare and detailed lists on forbidden socialist organizations. This variation allows me to use a flexible difference-in-differences as well as a shift-share approach. As mechanisms, I highlight that the socialist party evaded the repression by reallocating their activity and gained from the social insurance by claiming the credits for the welfare reform and providing a local cooperative alternative.
Keywords: D74; N44; P16; 330; welfare reform; repression; social democracy; opposition; voting; autocracy